Epithelial–mesenchymal plasticity and circulating tumor cells: Travel companions to metastases. Issue 3 (26th May 2017) - Francart, Marie‐Emilie; Lambert, Justine; Vanwynsberghe, Aline M.; Thompson, Erik W.; Bourcy, Morgane; Polette, Myriam; Gilles, Christine
Abstract : Epithelial–mesenchymal transitions (EMTs) associated with metastatic progression may contribute to the generation of hybrid phenotypes capable of plasticity. This cellular plasticity would provide tumor cells with an increased potential to adapt to the different microenvironments encountered during metastatic spread. Understanding how EMT may functionally equip circulating tumor cells (CTCs) with an enhanced competence to survive in the bloodstream and niche in the colonized organs has thus become a major cancer research axis. We summarize here clinical data with CTC endpoints involving EMT. We then review the work functionally linking EMT programs to CTC biology and deciphering molecular EMT‐driven mechanisms supporting their metastatic competence. Developmental Dynamics 247:432–450, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Understanding how EMT may functionally provide Circulating Tumor Cells (CTCs) with an enhanced metastatic competence is a major cancer research axis. We summarize here clinical data with CTC endpoints involving EMT. We review the work functionally linking EMT programs to CTC biology and deciphering molecular EMT‐driven mechanisms supporting their metastatic competence.